Ultra-High Performance Concrete Jacketing with Local Aggregates for Axial Strengthening of Reinforced Concrete Columns - Mardiana Oesman; Satrio Harry (JACEE (Journal of Advanced Civil and Environmental Engineering), 2025)
This study investigates the axial load performance of reinforced concrete (RC) columns strengthened with ultra-high-performance concrete (UHPC) jacketing incorporating locally sourced coarse aggregate. Four column specimens were tested, with variations in core concrete strength (20 MPa and 35 MPa) and jacketing material (normal concrete and UHPC). Monotonic axial compression tests were performed to evaluate load-bearing capacity, stiffness, ductility, energy absorption, and toughness. At 90 days, compressive strengths were 24.32 MPa for the 20 MPa concrete, 46.95 MPa for the 35 MPa concrete, and 80.06 MPa for the UHPC. Results demonstrate that UHPC jacketing significantly improved axial performance compared to normal concrete, particularly in terms of maximum load, stiffness, and toughness. However, higher-strength cores exhibited slightly reduced ductility. The findings underscore the potential of UHPC with coarse aggregate as a cost-effective strengthening material for existing RC columns, offering practical guidance for retrofitting strategies in developing countries.